Pedagogical Content Knowledge (Pck) in Mathematics of Four Year B.Sc B.Ed and Two Year B.Ed Trainees - Santosh Shah and Ramakanta Mohalik (Education India Journal: A Quarterly Refereed Journal of Dialogues on Education, 2015)
The pedagogical content knowledge of teachers has direct bearing on effective teaching and better student’s achievement. In this background, the investigators conducted this study to determine the level of PCK in mathematics of four year B.Sc B.Ed and 2 year B.Ed trainees and compare the level of PCK in mathematics of B.Sc B.Ed and 2 year B.Ed trainees. The investigator adopted descriptive method with sample of 67 trainees (39 from four year B.Sc, B.Ed and 28 from 2 year B.Ed) selected purposefully from trainees of the Regional Institute of Education, Bhubaneswar. Self developed PCK test consisting of 50 items basing on content knowledge in mathematics, knowledge of general pedagogy, understanding of learners and knowledge of educational contexts was used for studying PCK of trainees. The study found that i) 25.4% of total trainees have low PCK in mathematics, 43.3% of trainees have average PCK and 31.3% have high PCK in mathematics, ii) there is a significant difference in PCK of four year B.Sc B.Ed and 2 year B.Ed trainees at 0.01 levels, iii) there is no significant difference in PCK of male and female trainees in mathematics at 0.05 levels. The study has implications for changing both pre-service and in- service teacher education programmes.